A Systematic Review of Childhood Trauma and Cognitive Functioning in Individuals with Major Depressive Disorder (MDD) or Bipolar Disorder (BD) - Poormolaie , Mobina; Zomorodi, Saeedeh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aims to systematically investigate the relationship between childhood trauma and cognitive functioning in individuals diagnosed with Major Depressive Disorder (MDD) or Bipolar Disorder (BD). Methods and Materials: This study employed a systematic review approach, analyzing peer-reviewed English-language articles published between 2020 and 2025. A three-stage screening protocol was used: removal of duplicate records, evaluation of relevance to the research domain, and inclusion based on direct response to the research question. Comprehensive database searches were conducted using a combination of keywords related to childhood trauma, cognitive function, and mood disorders. Inclusion criteria required that studies involve participants aged 18 or older with a confirmed diagnosis of MDD or BD, assess objective cognitive outcomes, and establish a relationship with childhood trauma. Fifteen eligible studies were identified and analyzed based on variables such as study design, population characteristics, assessment tools, and outcomes. Findings: The included studies provided consistent evidence of significant associations between adverse childhood experiences (ACEs)—particularly emotional abuse and neglect—and structural and functional brain changes, including reduced gray matter, disrupted white matter integrity, and altered connectivity in regions involved in emotional regulation. These neural alterations were linked to impairments in memory, attention, executive functioning, and processing speed. Biological findings highlighted elevated levels of inflammatory markers (e.g., IL-6, TNF-α, CRP) and immune system dysregulation in individuals with childhood trauma histories. The cognitive effects and inflammatory responses varied across diagnostic groups, with some findings more pronounced in BD. Moderating factors such as family functioning, education, and medication type also influenced cognitive outcomes. Conclusion: This review underscores the critical role of childhood trauma in shaping cognitive deficits in mood disorders and calls for trauma-informed, multidisciplinary treatment strategies.